2006
DOI: 10.1111/j.1520-037x.2006.05339.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist‐Led Cardiac Risk Reduction Model

Abstract: The Cardiovascular Risk Reduction Clinic (CRRC) is a pharmacist-coordinated care model that incorporates the 4 major modifiable risk factors into a single treatment program. The authors aimed to assess the effectiveness of the CRRC model by comparing the Framingham point score before and after CRRC intervention. Retrospective data between 2001 and 2002 were analyzed for 375 veterans (age 65+/-10 years) with diabetes (88.8%) or coronary artery disease (44%) referred to the CRRC for intensive cardiac risk manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…In one study the advertising was targeted to males at high risk of CVD [36]. For a further two studies, participants were referred for CVD screening [24,30]. For the remaining study [32] participant recruitment was not clear.…”
Section: Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study the advertising was targeted to males at high risk of CVD [36]. For a further two studies, participants were referred for CVD screening [24,30]. For the remaining study [32] participant recruitment was not clear.…”
Section: Recruitmentmentioning
confidence: 99%
“…Pharmacist-led interventions have been shown to be feasible in a number of areas relevant to CVD, such as:  medication use [22];  management of CVD [23,24];  diabetes mellitus (DM) [25,26];  hypertension [27,28]; and  heart failure [29].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the majority of pharmacist CV intervention studies rely on physicians to identify patients eligible for the intervention. 2,7,12,14,15,18,19 Although this process can result in the optimization of drug therapy in selected patients, there is no way of knowing whether these individuals represent the entire at-risk population or those at the highest risk. Indeed, the missing link in many chronic disease management programs is the identification of patients who could potentially benefit from the intervention.…”
Section: Original Researchmentioning
confidence: 99%
“…Numerous studies have demonstrated benefits associated with incorporating pharmacists onto primary care teams to facilitate cardiovascular (CV) risk reduction. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] However, many such interventions are carried out in small numbers of patients.…”
mentioning
confidence: 99%
“…We have previously shown the success of this model in the simultaneous control of multiple cardiovascular risk factors in patients with diabetes mellitus or coronary artery disease (CAD). 7,8 Given previous research on the adverse effect of MHCs on cardiovascular risk reduction, we hypothesized that the presence of MHCs would attenuate the treatment efficacy of the CRRC on cardiovascular risk reduction in patients with diabetes. Therefore, we sought to compare the efficacy of the CRRC in the lowering of cardiovascular risk between those with and without MHCs.…”
mentioning
confidence: 99%